Integrated agriculture-aquaculture farming systems compilation of fisheries forum and contributed papers - Garcia, Manuel P. Jr. (Los Banos, Laguna PCAMRD, 1993)
PCAMRD Book Series no. 15/1993
Keywords: Fisheries; Farming systems; Aquaculture; Aquaculture; Agricultural systems